ChemInform Abstract: Enhanced Thermoelectric Properties of Earth‐Abundant Cu2SnS3 via in Doping Effect. Issue 25 (June 2016) - Tan, Qing; Sun, Wei; Li, Zhiliang; Li, Jing‐Feng
Abstract: Bulk samples of Cu2 Sn1‐x Inx S3 (x = 0—0.2) are prepared by mechanical alloying (450 rpm, 24 h) followed by spark plasma sintering in vacuum (873 K, 5 min).